2018
DOI: 10.1093/ons/opy143
|View full text |Cite|
|
Sign up to set email alerts
|

Occipital Artery to Extradural Vertebral Artery Bypass for Posterior Circulation Ischemia

Abstract: BACKGROUND Posterior circulation ischemic strokes can have devastating consequences, despite medical therapies. Extracranial–intracranial bypass for the augmentation of flow is a treatment option for selected patients with hemodynamic compromise and recurrent ischemia. However, posterior circulation bypass carries a higher risk and lower patency rate than bypass with anterior circulation. OBJECTIVE To present the occipital ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…For cases not amenable to endovascular treatment, or that have failed endovascular treatment surgical bypass procedures like occipital artery-VA bypass may be considered. 13 However, these procedures are technically challenging and require the patient to withstand surgery and its accompanying risks. In extensive vessel injury like transection, parent vessel has to be sacrificed as reconstructive approach is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…For cases not amenable to endovascular treatment, or that have failed endovascular treatment surgical bypass procedures like occipital artery-VA bypass may be considered. 13 However, these procedures are technically challenging and require the patient to withstand surgery and its accompanying risks. In extensive vessel injury like transection, parent vessel has to be sacrificed as reconstructive approach is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…55 For patients with posterior circulation vertebral artery disease, a single-center case series reported that surgical revascularization decreased recurrent stroke and death as compared with medical therapy alone, but no RCTs have been performed to establish efficacy and the procedure is considered investigational. 56,57 Indirect Bypass…”
Section: Direct Bypassmentioning
confidence: 99%
“…A surgical bypass has been previously shown as a possible treatment option in selected patients with posterior ischemic stroke. 28,29 However, whether bypass surgery, which was performed in patient 5, constitutes a therapeutic option for initial treatment or ought to be resolved as a last-line emergency treatment remains an individual decision. Lastly, a conservative treatment (patient 2) may be successful in cases, in which positional changes induce mechanical stress on brain supplying arteries.…”
Section: Discussionmentioning
confidence: 99%